Effect of melt flow rate and S/L interface on the P horizontal distribution in silicon. (August 2021) - Li, Pengting; Hu, Zhiqiang; Wang, Zilong; Wen, Shutao; Li, Jiayan; Jiang, Dachuan; Tan, Yi
Abstract: Uniform doping of phosphorus (P) in silicon is always the key and difficult point in the study of n-type solar cells. This paper aims to study the influencing factors for horizontal distribution for P. It is found that the distribution of P in silicon ingot is the results of the combined effect of melt flow and solid-liquid (S/L) interface. With numerical simulation, the melt flow rate in the edge is lower than that of the middle area, which leads to a higher effective segregation coefficient (Keff ). For the slightly concave S/L interface, the concentration of P in the molten silicon is lower when the solidification process began at the edge position. The higher Keff and lower concentration make the slightly concave interface has better performance in uniform doping at the early stage of growth. In addition, with the melt flow taken into account, a mathematical model was built to predict P concentration in the molten silicon. This work is helpful to explain the movement of P and achieve uniform distribution in the silicon ingot during production. Highlights: The melt flow field of directional solidification was investigated by the numerical simulation method. The influence of melt flow and S/L interface on the distribution of P was discussed. At the early stage of growth, the slightly concave interface performed better for uniform doping. A revised Scheil's equation considering the evaporation and segregation of P was proposed.